Improvement of Low Plasticity Clayey Soils Using Polypropylene Fibers - Senol A.; S.B., Ikizler; Etminan E.; Demir G. (American Society of Civil Engineers (ASCE), 2014)
Because highways are the most common and the most advanced means of transport compared to other transportation systems in Turkey, alternative techniques and materials are constantly being investigated to develop innovative solutions for the construction of highway embankments and other types of earth structures. It is obvious that in highway projects, excavation, loading, and transportation costs of the material are the most important factors for the total cost, and improvement in subgrade soils would have significant economical side effects. In this research, extensive laboratory experiments have been performed to investigate the use of polypropylene fibers with the scope of two different low plasticity clay soils obtained from Sile (Istanbul city region) and Kitre (Bayburt city region) districts of Turkey. Various soils and polypropylene fiber mixtures were prepared in the laboratory and the engineering properties of these mixtures were observed. The compaction characteristics and the unconfined compressive strength of samples were investigated. This paper illustrates the findings from the laboratory study with particular emphasis on the use of mentioned additive that provide economic benefits, as well as reduced environmental impact.